Brain Changes and Placebo. - Mueller, René J. (American Journal of Psychiatry, 2003)
A commentary on Helen S. Mayberg et al.'s “The functional neuroanatomy of the placebo effect,” which appeared in the American Journal of Psychiatry, vol. 159, 2002, pp. 728–37. A response by Mayberg et al. is also provided.